Madrid on the move : feeling modern and visually aware in the nineteenth century - Rodríguez-Galindo, Vanesa (Interventions: rethinking the nineteenth century, 2021)
'Madrid on the Move' offers an account of illustrated print culture and the urban experience in nineteenth-century Spain. It provides a fresh account of modernity from a transnational perspective. Drawing on different kinds of printed images and texts, it explores what being modern meant to people in their daily lives